The Impacts of Macroeconomic Factors on Exports : An empirical study between a developed and a developing economy, the case of France and Vietnam - Tironi, Clara Louise Paule; Sadílek, Tomáš; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis investigates how macroeconomic and trade-related factors influence export performance in France and Vietnam between 2000 and 2024, representing a developed and a developing economy respectively. By analyzing eleven indicators—including FDI, exchange rates, productivity, GDP, trade openness, and logistics metrics—through Simple and Multiple Linear Regression models, the study identifies key differences in how each economy responds to these determinants. Findings reveal that France’s export performance is more sensitive to individual macroeconomic variables, while Vietnam’s exports depend on the combined, systemic interaction of multiple factors, particularly FDI, productivity, and global demand. The research challenges conventional assumptions about developing economies’ vulnerability to single indicators and underscores the importance of integrated policy strategies to enhance export competitiveness.
Vedoucí práce: Tomáš Sadílek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses